SIMULATION MODEL OF UNMANNED AERIAL VEHICLE MAINTENANCE - Baturina, Natalia (Veredas do Direito, 2026)
A review of modern methods and approaches to UAV research is provided. In the context of the digital transformation of the maintenance process, the advantages of using the AnyLogic multi-approach environment for solving operational reliability problems are substantiated. The integration of AnyLogic discrete-event components for describing maintenance processes and agent-based logic for representing the life cycle of each individual drone allows for highly accurate prediction of service infrastructure bottlenecks and minimization of aircraft system downtime under intensive operating conditions. This paper explores the use of the AnyLogic environment to optimize maintenance processes and improve the operational readiness of aircraft. A comprehensive simulation model of the maintenance system is proposed, combining a discrete-event approach and agent-based modeling. This paper explores the use of the AnyLogic environment to optimize maintenance processes and improve the combat readiness of aircraft. A comprehensive simulation model of the maintenance system is proposed, combining a discrete-event approach and agent-based modeling. Algorithms for dynamic resource management of repair units are implemented. The model allows for assessing UAV fleet availability factors based on preventive maintenance strategies and onboard equipment failure rates, and determining resource allocation (technical personnel, equipment, and parts) under both scheduled and predictive maintenance conditions. It can be used to select maintenance strategies, manage resources, forecast operational availability, and optimize maintenance schedules.